Teaching Model of the Algemeene Middelbare School A-1 Eastern Literature Major (AMS A-1) in Solo, 1926-1932 - Heri Priyatmoko; Singgih Tri Sulistiyono; Dhanang Respati Puguh (Paramita: Historical Studies Journal, 2025)
Abstract: This article aims to analyze the development of the teaching model used and developed at the Algemeene Middelbare School A-1 (AMS A-1), majoring in Eastern Literature. The AMS A-1 in Solo in the Dutch East Indies was a unique historical phenomenon in colonial education. The teachers at this educational institution, which was created by the colonial government in 1926, developed an interactive teaching model inside and outside of class. This article uses the historical method to analyze its development and influence on the students. Teaching outside class was a new concept in the early 20th century in the colonized Indonesian archipelago, because the learning process usually only occurred inside classes and laboratories. The AMS A-1 senior high school students were invited on annual field trips to visit the temples their ancestors built, forming their cultural heritage. The goal of this model was to see up close indigenous cultural heritage, which they normally only knew from their textbooks, to dispel traditional myths about the places, and to further the bond between student and teacher. Besides that, it created a certain pride when learning about this heritage. This learning activity implicated the growth of Indonesian cultural nationalism, which became a means to push back against colonialism. The AMS A-1 institution thus became a boomerang for the Dutch colonial government. Abstrak: Artikel ini bertujuan untuk menganalisis perkembangan model pembelajaran yang digunakan dan dikembangkan di Algemeene Middelbare School A-1 (AMS A-1) jurusan Sastra Timur. AMS A-1 yang terletak di kota Solo, Hindia Belanda, merupakan fenomena sejarah yang unik dalam pendidikan kolonial. Para guru di lembaga pendidikan yang didirikan oleh pemerintah kolonial pada tahun 1926 ini mengembangkan model pembelajaran interaktif di dalam dan luar kelas. Artikel ini menggunakan metode sejarah untuk menganalisis perkembangan dan pengaruhnya terhadap siswa. Pembelajaran di luar kelas merupakan konsep baru di awal abad ke-20 di kepulauan Indonesia yang dijajah, karena proses pembelajaran biasanya hanya berlangsung di dalam kelas dan laboratorium. Siswa SMA AMS A-1 diajak untuk melakukan kunjungan lapangan tahunan untuk mengunjungi candi-candi yang dibangun oleh nenek moyang mereka, yang merupakan warisan budaya mereka. Tujuan dari model ini adalah untuk melihat dari dekat warisan budaya asli, yang biasanya hanya mereka ketahui dari buku pelajaran, untuk menghilangkan mitos tradisional tentang tempat tersebut, dan untuk mempererat hubungan antara siswa dan guru. Selain itu, hal ini menciptakan kebanggaan tersendiri ketika mempelajari warisan ini. Kegiatan belajar mengajar ini berimplikasi pada tumbuhnya nasionalisme budaya Indonesia yang menjadi sarana untuk melawan kolonialisme. Lembaga AMS A-1 dengan demikian menjadi bumerang bagi pemerintah kolonial Belanda.